Surficial sedimentary properties of Makran accretionary prism and its application to natural gas hydrate distribution - Wang, Haifeng; Yi, Liang; Wang, Fenlian; Li, Yibing; Cai, Yun; Zhang, Zhen; Yu, Miao; Deng, Xianze; Yang, Yong; Yao, Huiqiang; Deng, Xiguang; He, Gaowen (Frontiers in Marine Science, 2025)
The Makran accretionary prism (MAP) resulted from the low-angle, slow-rate subduction of the Arabian Plate beneath the Eurasian Plate. The MAP is an active continental margin, with natural gas hydrate (NGH). In this study, we report an integrated study on surficial sediments, in terms of sediment grain-size, clay minerals and elements. The main results are as follows: (1) the surficial sediments were mainly controlled by hydrodynamic conditions of the Indus River. Along the Indus River channel, it is mainly infilled with silt, while clays are mainly distributed in the accretionary prism. The turbidity records gradually decrease from east to west, along the Indus River channel. (2) Illite and chlorite are the dominate clay minerals, indicating that the surficial sediments were mainly from weathering processes in the Himalaya by the Indus River transport. The very-low contents of kaolinite and smectite indicate the lack of sediments from the Deccan Traps and the in situ hydrothermal materials. (3) Elements analysis indicates that elements Al, Mg, K, Fe, and Ti were terrigeneous, mainly distributed in the northern MAP, while elements Ca and P were from biogenic sources, mainly distributed in the southern part of the study area. In addition, elements U and Mo distribute generally coupled with bottom simulating reflector (BSR), which can be used as proxies of NGH identification. Therefore, we proposed that the covariation between NGH distribution, BSR identification, and trace elements Mo and U holds the potentials in NGH investigation.